Spatial Variation of Pine Tree-Ring Growth in the Solovetsky Islands - E. A. Dolgova; O. N. Solomina; V. V. Matskovsky; A. S. Dobryansky; N. A. Semenyak; S. S. Shpunt; Е. А. Долгова; О. Н. Соломина; В. В. Мацковский; А. С. Добрянский; Н. А. Семеняк; С. С. Шпунт (Izvestiya Rossiiskoi akademii nauk. Seriya geograficheskaya, 2019)
The paper presents the results of an analysis of the spatial variability of pine tree-ring growth in the Solovetsky Islands. As a result of the field work, tree-ring network containing 14 dendrochronological pine sites in various habitats were developed. For each site, a local tree-ring width pine chronology (from 472 to 271 years) is obtained, representing pine growth features in different habitat conditions. A comparison between chronologies revealed synchronious growth of pine in various habitats in the late 17th, in the first half of the 18th and the beginning of the 19th centuries. The use of cluster analysis allowed to identify several groups of chronologies with similar characteristics. So, trees growing on swamps, on a sandy substrate and in a green-moss pine forest or in a mixed forest are allocated in separate clusters. This clustering is also confirmed by the results of a dendroclimatic analysis of local chronologies. It turned out that the increase in the pine’s growth in the mixed forest and in the green-moss pine forest depends on the July air temperature variation. Inside this group, samples from pine forests have a common feature — a positive relationship of growth with the precipitation of September. The only site located on the sands showed a different climatic signal than the other chronologies, namely, the dependence on the temperature of August. В работе представлены результаты анализа пространственной изменчивости прироста сосны на территории Соловецких островов. В результате проведенных экспедиционных работ было заложено 14 дендрохронологических площадок сосны в различных местообитаниях. Для каждой из площадок получена локальная хронология по ширине годичных колец сосны продолжительностью от 271 до 472 лет, которая отражает особенности прироста в каждом местообитании. Сравнение, проведенное между хронологиями, выявило синхронность прироста сосен из различных местообитаний в конце XVII, в первой половине XVIII и в начале XIX вв. Применение кластерного анализа позволило выделить несколько ...